Securing the schoolyard: protocols that promote safety and positive student behaviors - Young, Nicholas D. (Rowman & Littlefield, 2019)
From grade school to guns: the history of violence in American schools -- Actions around the world: cross-cultural perspectives on student safety -- Bad behavior in school and cyberspace: bullying and its role in school violence -- What we see is what we get: the role of society and the media in school violence -- Protocols that protect: a successful systems to ensure school a safety -- All are invited: addressing the needs of marginalized student populations -- Strong partners in prevention: school-community-police relations.